Encouraging Knowledge Sharing Through Social Media: A Systematic Analysis of Drivers and Influences - M. Mushlih Ridho; Cakra Wirabuana; Dana Indra Sensuse; Imairi Eitiveni; Deden Sumirat Hidayat; Sofiyanti Indriasari (Eduvest - Journal of Universal Studies, 2025)
This study systematically investigates the dynamics of knowledge sharing on social media, focusing on identifying driving factors and their impacts. By employing a conventional literature review method and the PICOC structure, this research analyzed 73 studies from 2019 to 2024, revealing key insights into the role of social media in facilitating knowledge sharing. The findings categorize drivers into technological, social, motivational, knowledge-based, and organizational factors, each playing a significant role in enhancing or hindering knowledge sharing activities. The technological infrastructure and user-friendly interfaces, coupled with social dynamics, motivational incentives, the quality of knowledge, and organizational support, emerged as pivotal in propelling knowledge sharing. Conversely, challenges such as privacy concerns, information overload, and the threat of misinformation highlight the need for cautious optimization. This study contributes to the academic and practical understanding of knowledge sharing on social media, offering a foundation for future research and strategies to maximize its potential for innovation and organizational learning.